2006
DOI: 10.1088/0953-8984/18/29/012
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Stokes emissions and determination of Stark sub-level diagram of Er3+ions in KY3F10

Abstract: We are interested, in this work, in determining the Stark sub-level of Er 3+ ions doping a KY 3 F 10 single crystal with a molar concentration of 1%. We have used a new method of measurement of energies of the ground level and emitting levels from excitation and anti-Stokes emission spectra recorded at liquid nitrogen temperature. This technique is based on a spectral analysis of the anti-Stokes emissions recorded after selective excitation with a red dye tunable laser. Thus, we could determine the Stark sub-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Trivalent rare-earth ions (RE 3+ ) introduced into the lattice replace the Y 3+ ions, resulting in a C 4v symmetry centre [2]. RE 3+ ions for which the most comprehensive studies have been reported in KY 3 F 10 crystals include Pr 3+ [4], Sm 3+ [5], Eu 3+ [6][7][8], Er 3+ [9][10][11], Tm 3+ [12] and Yb 3+ [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trivalent rare-earth ions (RE 3+ ) introduced into the lattice replace the Y 3+ ions, resulting in a C 4v symmetry centre [2]. RE 3+ ions for which the most comprehensive studies have been reported in KY 3 F 10 crystals include Pr 3+ [4], Sm 3+ [5], Eu 3+ [6][7][8], Er 3+ [9][10][11], Tm 3+ [12] and Yb 3+ [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…One of the earlier works on rare-earth doped KY 3 F 10 comprehensively treated the Eu 3+ ion [6][7][8] with crystal-field and Judd-Ofelt analyses used as a basis for an analysis of radiative lifetimes and non-radiative relaxation. Likewise several studies have been performed utilizing the erbium ion [9][10][11] and these have tended to focus upon analysis of the crystal-field levels of Er 3+ using subtly different experimental techniques. Absorption and emission studies of KY 3 F 10 :Tm 3+ are reported [12]; crystalfield energy levels for the multiplets from 3 H 6 to 1 D 2 are presented together with the corresponding calculated levels and lifetimes for some of the multiplets.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, KY 3 F 10 exhibit useful laser and luminescence properties when doped with Er 3+ , Eu 3+ , Ho 3+ and Pr 3+ [4][5][6][7][8][9][10][11]. Usually, these properties are sensitively related to the local environment (e.g., bonding length and angles) for these rare-earth impurities on the Y 3+ site.…”
Section: Introductionmentioning
confidence: 99%